Celecoxib-Loaded Solid Lipid Nanoparticles for Colon Delivery: Formulation Optimization and In Vitro Assessment of Anti-Cancer Activity - Hamdan N. Alajami; Ehab A. Fouad; Abdelkader E. Ashour; Ashok Kumar; Alaa Eldeen B. Yassin (MDPI AG, 2022)
This work aimed to optimize a celecoxib (CXB)-loaded solid lipid nanoparticles (SLN) colon delivery system for the enhancement of anticancer activity. An ultrasonic melt-emulsification method was employed in this work for the preparation of SLN. The physical attributes were characterized for their particle sizes, charges, morphology, and entrapment efficiency (%EE), in addition to DSC and FTIR. The in vitro drug release profiles were evaluated, and the anticancer activity was examined utilizing an MTT assay in three cancer cell lines: the colon cancer HT29, medulloblastoma Daoy, and hepatocellular carcinoma HepG2 cells. All of the prepared SLN formulations had nanoscale particle sizes ranging from 238 nm to 757 nm. High zeta-potential values (mv) within −30 s mv were reported. The %EE was in the range 86.76-96.6%. The amorphous nature of the SLN-entrapped CXB was confirmed from SLN DSC thermograms. The in vitro release profile revealed a slow constant rate of release with no burst release, which is unusual for SLN. Both the F9 and F14 demonstrated almost complete CXB release within 24 h, with only 25% completed within the first 5 h. F9 caused a significant percentage of cell death in the three cancer cell lines tested after 24 h of incubation and maintained this effect for 72 h. The prepared CXB-loaded SLN exhibited unique properties such as slow release with no burst and a high %EE. The anticancer activity of one formulation was extremely significant in all tested cancer cell lines at all incubation times, which is very promising.